Cervical cancer screening and treatment capacity: A survey of members of the African Organisation for Research and Training in Cancer (AORTIC) - Linus Chuang; Nicole Rainville; Maureen Byrne; Thomas Randall; Kathleen Schmeler (Elsevier, 2021)
Background: Cervical cancer is the second most common cancer among women in Africa, and in half of the sub-Saharan African countries, it is the most common cancer. Currently, there are scarce resources and limited infrastructure to support cervical cancer screening and treatment in many African countries. Objectives: The aim of this study is to investigate the capacity of cervical cancer screening and treatment among members of the African Organization for Research and Training in Cancer (AORTIC). Methods: Data were collected from 183 participants through online surveys over a 3-month study period in 2016. Results: The respondents reported large variations among different African countries. This study highlights the differences between African countries in the availability of screening programs as a result of the resources allocated to healthcare development. Radiation therapy capacity remained the most limited treatment modality available, followed by the lack of gynecologists or gynecologic oncologists who can perform radical hysterectomy. Conclusions: This information is critical for physicians, public health educators, and policymakers aiming to improve the outcomes among women with cervical cancer in Africa.